Is Ciliary Muscle Affected in Migraine Patients with Aura and without Aura? - KIVANÇ, SERTAÇ ARGUN; Ulusoy, Mahmut Oguz; Akova-Budak, Berna; Olcaysu, Osman Okan; Ozcan, Muhammed Emin (My University, 2015)
Background: The aim of this study was to compare spherical equivalents (SE) and spherical equivalents with cycloplegic (CSE) values of migraine patients with and without visual aura, with those patients without migraine complaints.